PENDAMPINGAN BERBASIS LOKALITAS : UPAYA KOLEKTIF MENCEGAH STUNTING DI KOMUNITAS - Fitriyah, Ries Dyah; Anggraini, Selviana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Stunting is an urgent problem that needs to be resolved as soon as possible in Banyuanyar Regency. Based on the data, there is a tendency for increases and decreases each year, the peak increase in stunting prevalence rates was in 2021 when 147 people experienced stunting, in the following year, namely 2022, the stunting prevalence rate decreased to 93 people and this number increased in the following year. namely in 2023 there will be 128 people. The aim of this research is to explore stunting prevention efforts that have been carried out by the government and community groups. The method used in this research is qualitative research which prioritizes descriptive data for analysis according to the reality in the field. The results of this research found several strategic efforts made by the Banyuanyar District government to prevent stunting, namely collaborating with health institutions in Klenang Kidul Village and collaborating with universities, to accelerate efforts to prevent stunting. The business efforts carried out are 1). Early marriage prevention program, 2). Socialization starts from teenagers to pregnant women, 3). TPPS (Stunting Reduction Acceleration Team), 4). AKS (Stunting Case Audit) team program, 5). Providing intervention in the form of PMT, 6). Routine posyandu activities for toddlers and pregnant women, 7). Stunting prevention program with MPASI.